I assume the first problem is really 8^(-2x+4)=64

take log_{8}of both sides

log_{8}(8^{-2x+4})=log_{8}(64)

which leads to

(-2x+4)log_{8}(8)=2log_{8}(8)

(-2x+4) = 2

x = 1

second problem

I would first rewrite log_{9}x=1/2 as (ln(x))/(ln(9))=1/2

then

ln(x) = (1/2) ln(9)

ln(x) = ln(9^{1/2})

x = 9^{1/2}=3

third

first rewrite as

(ln(x-1) + ln(x+1))/(ln3)=1

ln(x-1)+ln(x+1) = ln3

ln(x^{2}-1)=ln3

x^{2}-1=3

x^{2}=4

x=2

x can't be -2 because it would cause you to take the log of a negative number

ln=natural log